2020
DOI: 10.1590/1984-0462/2020/38/2018338
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Adherence Among Children and Adolescents in a Cystic Fibrosis Reference Center

Abstract: ABSTRACT Objective: To evaluate the level of self-referenced treatment adherence (TA) and its association with clinical and sociodemographic variables in patients with cystic fibrosis assisted at a reference center, as well as compare the level of self-referenced TA with that presumed by the multidisciplinary team. Methods: This is a cross-sectional study that included children and adolescents aged between 0-20 years with cystic fibrosis. Adolescents older than 14 years or their guardians, when you… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
0
1
0
Order By: Relevance
“…The good adherence of children and adolescents to these programmes demonstrates their acceptability and allows us to predict the potential of e-health interventions for solving problems present in these chronically ill patients. Some studies have observed that adherence is unsatisfactory, especially in certain therapeutic modalities, such as nutritional guidelines, inhalation therapy, and respiratory physical therapy [1,7,9,33].…”
Section: Discussionmentioning
confidence: 99%
“…The good adherence of children and adolescents to these programmes demonstrates their acceptability and allows us to predict the potential of e-health interventions for solving problems present in these chronically ill patients. Some studies have observed that adherence is unsatisfactory, especially in certain therapeutic modalities, such as nutritional guidelines, inhalation therapy, and respiratory physical therapy [1,7,9,33].…”
Section: Discussionmentioning
confidence: 99%
“…Sendo assim, a presente pesquisa justificou-se pela demanda de pacientes que necessitavam desse modelo assistencial, visto a urgência em manter o tratamento fisioterapêutico aos indivíduos com FC, uma vez que a não adesão ao manejo nessa doença contribui para o prolongamento do tempo de internação, maior ocorrência de exacerbações pulmonares e perda da função pulmonar, sendo esta sua principal causa de óbito. 12,13,14 Desse modo, buscou-se colher informações e feedback de pacientes e seus responsáveis quanto a esta nova modalidade da fisioterapia, visando melhorar as principais insatisfações e adequar o programa ao perfil de cada indivíduo, no intuito de facilitar a adesão e contribuir na manutenção da QV. 13,14 No entanto, conforme resultado apresentado, poucos participantes retornaram com as respostas, o que comprometeu, inclusive, a condução do método proposto e a captação dos resultados da investigação.…”
Section: Discussionunclassified
“…12,13,14 Desse modo, buscou-se colher informações e feedback de pacientes e seus responsáveis quanto a esta nova modalidade da fisioterapia, visando melhorar as principais insatisfações e adequar o programa ao perfil de cada indivíduo, no intuito de facilitar a adesão e contribuir na manutenção da QV. 13,14 No entanto, conforme resultado apresentado, poucos participantes retornaram com as respostas, o que comprometeu, inclusive, a condução do método proposto e a captação dos resultados da investigação.…”
Section: Discussionunclassified
“…Водночас показники прихильності щодо рекомендацій МДТ серед педіатрич-ного населення досить низькі, незважаючи на несприятливі наслідки недотримання приписаної дієти. Але дослідженнями різних хронічних захворювань у дітей, які потребують суворого дотримання рекомендацій МДТ, встановлено, що зміна харчування є однією з найтяжчих змін поведінки [1,4,5,7,8,12,17,19,[20][21][22][23]. Ці труднощі обумовлюють необхідність додаткового консультування поведінковими педіатрами та психологами.…”
Section: вступunclassified
“…Незважаючи на важливість високої прихильності до приписаної дієти, кількість досліджень щодо дотримання специфічних дієтичних рекомендацій дітьми з МВ обмежена [4,6,7,17,20,21].…”
Section: вступunclassified